2011
DOI: 10.2478/v10182-011-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Effects on Photosynthesis, Chlorophyll Fluorescence and Water Relations in Tolerant and Susceptible Chickpea (Cicer Arietinum L.) Genotypes

Abstract: In order to evaluate morphological and physiological traits related to drought tolerance and to determine the best criteria for screening and identification of drought-tolerant genotypes, we grew two tolerant genotypes (MCC392, MCC877) and two sensitive genotypes (MCC68, MCC448) of chickpea under drought stress (25% field capacity) and control (100% field capacity) conditions and assessed the effect of drought stress on growth, water relations, photosynthesis, chlorophyll fluorescence and chlorophyll content i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
114
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 21 publications
15
114
0
5
Order By: Relevance
“…Reduction in transpiration rate is a plant response that indicates water conservation and reduced water loss through stomata (Jones et al, 1985). Various studies revealed that transpiration rate decreased under drought stress (Egret and Tevini, 2002;Rahbarian et al, 2011), which possibly resulted from reduced photosynthetic rate and stomatal conductance in drought affected plants as happened in present study. Our results regarding free proline content are in agreement with those reported by Unyayar et al (2009) who revealed that high concentration of free proline content in sunflower leaf becomes a solute under drought stress and play its role in intercellular osmotic adjustment.…”
Section: Discussionsupporting
confidence: 63%
“…Reduction in transpiration rate is a plant response that indicates water conservation and reduced water loss through stomata (Jones et al, 1985). Various studies revealed that transpiration rate decreased under drought stress (Egret and Tevini, 2002;Rahbarian et al, 2011), which possibly resulted from reduced photosynthetic rate and stomatal conductance in drought affected plants as happened in present study. Our results regarding free proline content are in agreement with those reported by Unyayar et al (2009) who revealed that high concentration of free proline content in sunflower leaf becomes a solute under drought stress and play its role in intercellular osmotic adjustment.…”
Section: Discussionsupporting
confidence: 63%
“…Impaired mitosis, limited cell elongation and expansion result in reduced plant height, leaf area and the crop yield of plants growing under drought Days after treatment application Days after treatment application stress. Therefore, the increased chlorophyll content under drought stress may be related to a decrease in the leaf area (Rahbarian et al, 2011). Figure 6 shows that the concentration of leaf N remains nearly constant from 2 kPa suction head up to 200 kPa suction head.…”
Section: And Discussionmentioning
confidence: 85%
“…Chlorophyll degradation and/or chlorophyll synthesis deficiency occur when plants are subjected to drought stress (Ahmed et al, 2009;Rahbarian et al, 2011;Guo et al, 2016). According to Hussein et al (2008) drought stress resulted in chlorophyll content increase, while Farhad et al (2011), Pirzad et al (2011 and Ma et al (2015) did not observe any significant changes in its content.…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…It affects metabolic processes and gas exchange parameters (stomatal conductance, internal CO2 concentration and permeability of cell membrane) (Yordanov et al, 2000). One of the first responses of a plant to drought stress is stomatal closing, which results in limited water loss (Galmes et al, 2007a;Rahbarian et al, 2011). Decreasing internal CO2 concentration (Ci) and inhibition of ribulose-1, 5-bisphosphate carboxylase/oxygenase enzyme activity and ATP synthesis lead to a decrease in net photosynthetic rate under drought stress (Dulai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%